Carbogen gas and radiotherapy outcomes in prostate cancer. (February 2013) - Yip, Kent; Alonzi, Roberto
Prostate cancer hypoxia is associated with inferior prognosis and resistance to treatment. The use of androgen deprivation therapy, both prior to and during radiotherapy, may exacerbate underlying hypoxia. Whilst larger radiation doses per fraction may achieve therapeutic gain, this is balanced by the reduced opportunity for re-oxygenation to take place during the course of treatment. Improving the underlying hypoxic tumour environment may therefore improve the treatment outcomes. Strategies to combat tumour hypoxia, with particular focus on the use of carbogen gas breathing concurrently with radiotherapy, is the subject of this review.